Pengaruh Kepercayaan, Komitmen dan Komunikasi Terhadap Retensi Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Nasabah Bank BRI Unit Kartini Semarang) - Fitria Sulistiani; Naili Farida; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
The background of this study is banking bussines industry growing. That thing makes competition between banking competitor tighter. PT Bank Rakyat Indonesia (Persero) Tbk is one of the corporation that move on financial related service which bigger and has widest connection in Indonesia.The purpose doing this research is to knowing reliance influence. Commitment and communication cutomers’s retention with customers’s satisfactory as intervening variable to customer of BRI bank Kartini Semarang unite. Research type that used in this research is explanatory research, with data collecting technique by quetioner and interview. Sample taking technique using non probability sampling technique that is purposive sampling with number of samples are 100 respondens who they are customers of BRI bank Kartini Semarang unite. Analysis methode which used in this research using regretion analysis two steps which SPSS For Windows version 16.0 help, which before did validty and reliability test firstly.This research result shows that reliance, commitment, and communication partially has positive influence and significant customers satisfactory and customer satisfactory has positive influence and significant to customers retention. Based on two steps regretion analysis result can be conclude that to increase customers retention, corporation management need pay attention reliance factor, commitment, communication and customers satisfactory because of that factors proved to be influence customers retention.